Characterization of composite partition board using basalt rock and coir fibre - I Made Dwi Litarona; Putu Cinthya Pratiwi Kardita; I Kadek Delon Putra Setiawan; Ni Luh Wayan Inten; Faradila Sahara Ramandhani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The increasing global demand for housing and building materials is creating pressure for sustainable alternatives, driven by the massive generation of construction waste and the use of non-eco-friendly materials. The main purpose of this study was to analyse the characteristics of a composite partition board utilizing basalt rock offcuts with over 96 tons by 2019, and coir fibre waste, which reaches approximately 1.8 million tons annually, as alternative materials. The resulting composite boards were designed to substitute fine aggregate with basalt rock waste and utilized coir fibre as an additive. A key finding is the inverse relationship between coir fibre content and composite density, where the reduction of coir fibre significantly improved the physical properties. Analysis showed that all variations significantly exceeded the minimum requirements specified in the SNI 03-2104-1991 and JIS A 5417-1992 standards for density and dimensional stability. Specifically, the fibre free K2 composition achieved the highest density of 1.87 g/cm3, classifying it as a superior high quality cement board. Furthermore, all compositions demonstrated excellent durability, with impact resistance exceeding 99% mass retention and thermal stability up to 200°C, confirming the composite’s potential as a sustainable, high-performance alternative to conventional partition materials. This study provides a practical contribution to green construction research by validating a localized dual-waste composite that meets international building codes, thereby operationalizing the objectives of SDG 9 and 12 through industrial and agricultural waste utilization.